Economics of Human Resource: Depth Classification Version of CC - Neelameghan, A. (Journal of Information and Knowledge, 1972)
A depth classification version of Colon Classification for compound subjects going with the Host Subject "X2,Y Resource, Human" is given. The methodology of design is based on that for freely faceted classification. Economy in schedule building has been secured by using devices such as, Geographical Device and "Divide-like" Device. An index to the schedule, a list of fifty examples classified according to the depth version, and an alphabetical index to the classified list are given.